ANALISIS SISTEM PENGENDALIAN INTERNAL ATAS PEMBIAYAAN MURABAHAH PADA BRI SYARIAH KC MANADO - Khoirunnisaa, Ummu Almaas; Manossoh, Hendrik; Afandi, Dhullo (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Murabaha is a sale and purchase agreement with the selling price of goods at cost plus an agreed profit which the seller must disclose the cost of the goods to the buyer. The purpose of this research is to analyze the internal control system applied to BRI Syariah KC Manado whether it has been effective and in accordance with the principles of COSO (Committee Of Sponsoring Organizations). Data analysis method of this research is using descriptive analysis that compares the results of observations, interviews, document analysis established by the company with existing theory. Data collection methods in this study are interviews, observation, and document review. The results shows that internal controls applied for murabahah financing at BRI Syariah KC Manado include rules set by management, organizational structure, forms and documents used in murabahah financing, recording of legitimate financing transactions, and monitoring of financing. Internal control of murabahah financing at BRI Suyariah KC Manado has been running quite well. But in application still found weaknesses that can hinder the implementation of internal controls in the company. Still found employees who do double job. This is not in accordance with the principle of COSO, where Commitment in the Competence of employees should be improved and more qualified in various areas of specialization. BRI Syariah KC Manado in applying internal controls can be affirmed and in accordance with the principles of COSO.Keywords: COSO, murabahah financing, internal control system.